IMF's Loan Conditionality: Negative Consequences in the Borrower Country and the Burden of Responsibility - Atta, Sara Mohamed Osama Abdalla (AUC Knowledge Fountain, 2021)
People often think that IFIs, such as the World Bank and the International Monetary Fund are prominent players in the global economy by providing funds to countries in need of development and sustainment of welfare, unfortunately these institutions can cause devastating effects in the borrower country. The harsh conditionality of the IMF plays a huge role in the negative economic consequences incumbent upon the borrower country. Meanwhile, the lack of legal remedies for private individuals suffering from the conditionality aggravates the consequences for these people. On the one hand, conditionality may strain the economy of the borrower country which leads to impeding the government’s ability to fulfill their international obligations to provide certain rights to their citizens. On the other hand, there are no available legal remedies for private individuals neither in the international sphere or the domestic one. Internationally, IFIs flee responsibility for the consequences of their policies in the borrower countries by escaping behind the lack of adequate internal remedy mechanisms within these institutions and behind the controversial adherence of the these institutions to the right to remedy established under customary international law and to human rights. Domestically, these institutions cannot be held accountable before domestic courts of the borrower country as they enjoy immunity. So the burden of responsibility for the consequences of policies and conditionality imposed by IFIs is shifted from the institution to the administrative bodies of the borrower state who implement the conditionality of the institutions. This paper argues that private individuals suffer from the negative consequences of loans conditionality given by IFIs by causing negative economic effects leading to violations to the rights of private individuals that are supposed to be guaranteed by international conventions due to the burden placed upon the borrower country. It further argues that the lack of remedies deprives private individuals of their rights, as a right with no remedy is no right at all.